Effectiveness of the Deep Learning Approach Assisted by Wordwall Media on Civics Education Learning Outcomes - Maulana, Arif; Susilo Tri Widodo (Jurnal Prima Edukasia, 2025)
Learning approaches and media that do not comply with Permendikbudristek Number 16 of 2022 on Process Standards have contributed to low learning outcomes. This study investigates the effectiveness of the deep learning approach supported by Wordwall media on Civics Education learning outcomes for Grade V students at Cahaya Bangsa Integrated Islamic Elementary School. Using a quasi- experimental design, the study involved 112 fifth-grade students from several elementary schools in the Ki Hajar Dewantara Cluster, Semarang. The sample was determined through cluster random sampling, with Class V-A as the experimental group and Class V-B as the control group. Data were collected through pre- and post-tests, observations, interviews, and documentation. Analysis included normality and homogeneity tests, followed by t-tests and N-Gain calculations. The results show a significant difference between groups, with the experimental class achieving a moderate N-Gain of 0.60 compared to 0.32 in the control class. These findings confirm that the integration of deep learning with Wordwall media positively impacts students’ performance and conceptual understanding. This study contributes to the field of education by providing empirical evidence that technology-supported deep learning can foster higher-order thinking, enrich Civics Education instruction, and offer innovative pedagogical models aligned with national standards at the elementary school level.